SERCA2a stimulation by istaroxime improves intracellular Ca2+ handling and diastolic dysfunction in a model of diabetic cardiomyopathy. Issue 4 (1st April 2021) - Torre, Eleonora; Arici, Martina; Lodrini, Alessandra Maria; Ferrandi, Mara; Barassi, Paolo; Hsu, Shih-Che; Chang, Gwo-Jyh; Boz, Elisabetta; Sala, Emanuela; Vagni, Sara; Altomare, Claudia; Mostacciuolo, Gaspare; et al.
Abstract: Aims : Diabetic cardiomyopathy is a multifactorial disease characterized by an early onset of diastolic dysfunction (DD) that precedes the development of systolic impairment. Mechanisms that can restore cardiac relaxation improving intracellular Ca 2+ dynamics represent a promising therapeutic approach for cardiovascular diseases associated to DD. Istaroxime has the dual properties to accelerate Ca 2+ uptake into sarcoplasmic reticulum (SR) through the SR Ca 2+ pump (SERCA2a) stimulation and to inhibit Na + /K + ATPase (NKA). This project aims to characterize istaroxime effects at a concentration (100 nmol/L) marginally affecting NKA, in order to highlight its effects dependent on the stimulation of SERCA2a in an animal model of mild diabetes. Methods and results : Streptozotocin (STZ) treated diabetic rats were studied at 9  weeks after STZ injection in comparison to controls (CTR). Istaroxime effects were evaluated in vivo and in left ventricular (LV) preparations. STZ animals showed (i) marked DD not associated to cardiac fibrosis, (ii) LV mass reduction associated to reduced LV cell dimension and T-tubules loss, (iii) reduced LV SERCA2 protein level and activity and (iv) slower SR Ca 2+ uptake rate, (v) LV action potential (AP) prolongation and increased short-term variability (STV) of AP duration, (vi) increased diastolic Ca 2+, and (vii) unaltered SR Ca 2+ content and stability in intact cells. Acute istaroxime infusion (0.11 mg/kg/min for 15 min) reduced DD in STZ rats. Accordingly, in STZ myocytes istaroxime (100 nmol/L) stimulated SERCA2a activity and blunted STZ-induced abnormalities in LV Ca 2+ dynamics. In CTR myocytes, istaroxime increased diastolic Ca 2+ level due to NKA blockade albeit minimal, while its effects on SERCA2a were almost absent. Conclusions : SERCA2a stimulation by istaroxime improved STZ-induced DD and intracellular Ca 2+ handling anomalies. Thus, SERCA2a stimulation can be considered a promising therapeutic approach for DD treatment. Graphical Abstract: